Kesesuaian Vegetasi untuk Taman Kota Semarang - Tri Martuti, Nana Kariada; Rahayuningsih, Margareta; Alfirdani, Khoirunisa (Life Science, 2021)
Fullfilling of Green Open Spaces through the arrangement of urban parks. Vegetation is an important element of urban parks. The incompatibility of the vegetation can reduce the function of the urban parks. The aim of this research is to analyse the suitability of vegetation in urban parks in Semarang. This research used exploration method. The results of key performance index analysis, show that the suitability of vegetation in urban parks of Semarang ranges from 56.25% to 84.3%. Assessment of vegetation’s suitabilities is influenced by physical characteristics, such as canopy, roots, color of flower, and others. The functions of vegetation such as shade plants, absorbent pollutants, increasing aesthetic value, spacing and composition of vegetation also can affect the suitability of vegetation in urban parks. The vegetation’s suitabilities in urban parks in Semarang can be categorized as compatible, compatible enough, and not compatible. Pemenuhan kebutuhan Ruang Terbuka Hijau (RTH) melalui penataan taman kota. Vegetasi merupakan elemen penting penyusun taman kota. Ketidaksesuaian vegetasi penyusun taman dapat menyebabkan berkurangnya fungsi taman kota. Penelitian ini bertujuan untuk menganalisis kesesuaian vegetasi yang ada di taman kota Semarang. Metode yang digunakan adalah eksplorasi. Hasil analisis key performance index menunjukkan kesesuaian vegetasi di taman kota Semarang berkisar antara 56,25% sampai dengan 84,3%. Penilaian terhadap kesesuaian vegetasi dipengaruhi oleh ciri fisik, seperti tajuk, perakaran, warna bunga dan lainnya. Fungsi dari tanaman seperti sebagai tanaman peneduh, penyerap polutan, penambah nilai estetika, arak tanam dan pengkomposisian tanaman dalam taman juga mempengaruhi kesesuaian vegetasi pada taman. Kesesuaian vegetasi di taman kota Semarang dapat dikategorikan sesuai, cukup sesuai dan kurang sesuai..